Characterization of resol resins modified by the addition of PVC plastisols - Manfredi, Liliana Beatriz (2005)
Plastisols, which are a blend of poly(vinyl chloride) resin and a plasticizer (DEHP), were used as a toughening agent of a resol resin in order to improve the mechanical properties. It was not possible to formulate resol blends by adding more than 10 % of plastisol owing to a lack of apparent homogeneity in the systems, which also showed many air bubbles. The relationship between dynamic mechanical, mechanical and thermal properties and the amount of plastisol added was studied. It was determined from the infrared spectroscopy and dynamic mechanical results that the resol-plastisol blends seem to be formed by a reaction between the phenol and PVC giving a higher crosslinked structure. An improvement in the thermal resistance of the blends at lower temperatures was observed with an increase in the percentage of plastisol. Flexural analysis showed the elastic behaviour of the systems. However, it was not possible to observe the effect of the plasticizer (DEHP) owing to the low quantity of plastisol that was added to the resol. © 2004 Society of Chemical Industry.